2015
DOI: 10.1007/s00330-015-3642-2
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive detection of cardiac amyloidosis using delayed enhanced MDCT: a pilot study

Abstract: • CT can detect abnormal first-pass and delayed enhancement in cardiac amyloidosis. • Measurement of relative myocardial enhancement between acquisitions helps to detect cardiac amyloidosis. • CT may provide useful data to diagnose cardiac amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…Several studies have reported that delayed contrast-enhanced computed tomography (DE-CT) imaging showed good agreement with LGE-CMR in patients with coronary artery disease [10][11][12], hypertrophic cardiomyopathy [13], and cardiac amyloidosis [14] because iodinated contrast material accumulates in the myocardial scar in a manner similar to that of gadolinium chelates [11,15]. Furthermore, DE-CT can be applied to patients with implantable devices [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that delayed contrast-enhanced computed tomography (DE-CT) imaging showed good agreement with LGE-CMR in patients with coronary artery disease [10][11][12], hypertrophic cardiomyopathy [13], and cardiac amyloidosis [14] because iodinated contrast material accumulates in the myocardial scar in a manner similar to that of gadolinium chelates [11,15]. Furthermore, DE-CT can be applied to patients with implantable devices [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Полученные нами данные о высокой информа-тивности МСКТ достаточно уникальны -нам встре-тилось лишь одно пилотное исследование 2015г, в котором метод был успешно применен у 13 больных амилоидозом сердца, получено 2 ложнонегативных и 3 ложнопозитивных результата [12]. МСКТ одно-временно позволяет исключить коронарный атеро-склероз, но выявление последнего не исключает ами-лоидоза.…”
Section: Discussionunclassified
“…ECV measured using EQ imaging has demonstrated promise as a biomarker of extracellular disease, able to quantify extracellular expansion resulting from diffuse fibrosis within the heart 2,11,13 and liver, 14,15 and amyloid protein deposition within various organs. 4,16,17 Although ECV has been validated against specific reference standard measures of disease severity, to date there has been no specific verification of this volume fraction. By using a 3D engineered tissue model we have been able to control the fractional cellular volume within a tissue and demonstrate in 6 collagen gels, that EQ-MRI provides good prediction of extracellular fraction.…”
Section: Discussionmentioning
confidence: 99%